A New Functional Model for Prediction of Chaperone Activity of the Recombinant M. tb Acr (α-Crystallin) Using Insulin as Substrate - Gautam Krishnan; Utpal Roy (Canadian Journal of Infectious Diseases and Medical Microbiology)
Mycobacterium tuberculosis Acr is an important protein expressed in latent tuberculosis which is active as an oligomer in preventing misfolding of cellular proteins. In this study, Mycobacterium alpha crystallin (acr) gene was cloned and expressed in Escherichia coli (E. coli). The recombinant Acr protein was purified by Nickel-NTA resin. The oligomeric state of Acr was confirmed by gel filtration chromatography using Sephacryl S-200 and Native-PAGE. Studies of chaperone activity were performed with insulin as a substrate at different mole ratios of Acr with 2 types of samples, His tag elutes (H) and His tag elutes with gel filtration (G). It was observed that the ratio of different sizes of oligomers (9 to 24 mers) had a significant effect on chaperone activity. Using the mole ratio of Acr for both (H) and (G) samples to insulin B chain and ratio of oligomers, we determined the number of Acr molecules binding to insulin as a model substrate. We found that if 1.5% of the insulin B chains are covered completely by the (G) samples, aggregation is completely inhibited as compared to 6% with (H) samples. Pre-heat treatment studies were carried out at 37°C, 60°C, and 70°C. Far-ultraviolet Circular Dichroism (UV-CD) analysis provided fresh insights into the role of β-sheets and α-helices in chaperone activity, particularly in (H) samples suggesting a reversible conformational transition from helices to sheets. This enabled us to formulate a functional model for binding of Acr to insulin B chains which incorporated 4 types of secondary structure molecules. This might be a useful tool for analyzing in vitro preparations of recombinant Acr and build more consensuses on the structure-activity relationship especially in terms of oligomeric ratios.